Pengaruh Faktor Resiko Terhadap Keterlambatan Penyelesaian Proyek Pembuatan 3 Unit Pergola Makam Sunan Drajat Lamongan - tri sutrisno (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2020)
ABSTRACTService providers involved in a project generally expect the project to be carried out to run smoothly, the evaluation of risk factors for project delay is necessary. This study departs from the formulation of the problem are How to rank (factors) the factors that influence the delay in the completion of the construction work project making 3 units of pergola (Tomb of SunanDrajat). And this study aims to determine the risk factors affect the delay in completion of the project of making 3 units of pergola (Tomb SunanDrajat). The method of study is quantitative research by using field observation research methods and also data collection using people who are experts on the project. The data collected is based on the answers from respondents distributed to 20 respondents taken at random. The data analysis in this study using the Validity and Reliability Test using SPSS 22 is valid and relable and then the data were analyzed using the F test and T test. The results showed an F test of 9,337 and a t-test (2,661) for financial risk variables ( X1), tcount (2.258) for resource risk variables (X2) and tcount (3.132) for design risk variables (X3).